Screening of interferon-stimulated genes against avian reovirus infection and mechanistic exploration of the antiviral activity of IFIT5 - Wang, Sheng; Wan, Lijun; Ren, Hongyu; Xie, Zhixun; Xie, Liji; Huang, Jiaoling; Deng, Xianwen; Xie, Zhiqin; Luo, Sisi; Li, Meng; Zeng, Tingting; Zhang, Yanfang; et al. (Frontiers in Microbiology, 2022)
Avian reovirus (ARV) infection can lead to severe immunosuppression, complications and secondary diseases, causing huge economic losses to the poultry industry. In-depth study of the mechanism by which the innate immune system combats ARV infection, especially the antiviral effect mediated by interferon, is needed for the prevention and control of ARV infection. In this study, the ARV strain S1133 was used to artificially infect 7-day-old specific pathogen–free chickens. The results showed that the ARV rapidly proliferated in the immune organs, including spleen, bursa of Fabricius, and thymus. The viral load peaked early in the infection and leaded to varying degrees of pathological damage to tissues and organs. Real time quantitative PCR showed that the mRNA levels of interferon and multiple interferon-stimulated genes (ISGs) in the spleen, bursa of Fabrics, and thymus were upregulated to varying degrees in the early stage of infection. Among the ISGs, IFIT5 and Mx were the most upregulated in various tissues and organs, suggesting that they are important ISGs for host resistance to ARV infection. Further study of IFIT5 showed that overexpression of IFIT5 gene inhibited replication of ARV, whereas inhibition of endogenously expressed IFIT5 gene by siRNA promoted replication of ARV. IFIT5 may be a positive-feedback regulator of the innate immune signalling pathways during ARV infection. It may induce IFN-α production by promoting the expression of MAD5 and MAVS to exert its antiviral effect. The results of this study help explain the innate immune regulatory mechanism of ARV infection and reveal the important role of IFIT5 in inhibiting ARV replication, which has important theoretical significance and practical application value for the prevention and control of ARV.